Do Financial Experts on the Board Matter? An Empirical Test From the United Kingdom's Non-Life Insurance Industry. (January 2020) - Adams, Mike; Jiang, Wei
We examine the relation between board-level financial expertise and six measures of performance using panel data drawn from the United Kingdom's non-life insurance industry. We find that collectively, financial experts have a beneficial influence on the performance outcomes of insurers. We also observe that board-level qualified accountants and actuaries are linked with superior performance in all six of our selected financial outcome measures. Professional insurance underwriters are associated with sound solvency levels (low leverage) and underwriting results, but not positive earnings-based measures. This suggests that underwriters may not be as adept at group-level earnings enhancement as accountants and actuaries. In addition, we find that the introduction of IFRS 4 in 2004/2005 did not have a significant impact on board composition and financial outcomes. Finally, we consider that our results could have commercial and/or policy implications.